[Стихи, рассказы] - Шагимарданов Никита (Библиотека "Известия Удмуртской Республики", 2009)
Экземпляры: Аб (20151124) / Инвентарный номер: 103310 / Цена: 10.00 / Авт.знак: Ш 15 / ГРНТИ: 17.82 / ББК: 84(2Рос=Удм)